2021
DOI: 10.3390/medicina57121370
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Retrospective Study to Assess the Short-Term Safety of Traditional Smooth or Microtextured Silicone Gel-Filled Breast Implants in Korea

Abstract: Background and objectives: We conducted this preliminary retrospective study to assess the short-term safety of silicone gel-filled breast implants (SGBIs) that are commercially available in Korean women. Materials and methods :The current retrospective, observational study was conducted in a total of 2612 patients (n = 2612) who underwent augmentation mammaplasty using breast implants at our hospitals between 1 January, 2017 and 31 August 2021. Results: Overall, there were a total of 248 cases (9.49%) of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…She complained of severe depressive symptoms, had a handful of hair fall every day, presented with insomnia, and was inclined to commit suicide [140]. The safety of the Motiva Ergonomix TM Round SilkSurface was confirmed in a cohort of Korean women, as previously described [85,86,141]. It was previously reported that the Motiva Ergonomix TM Round SilkSurface might be a device of choice for Korean women who faced a crisis from the first Korean case of a medical device fraud [86].…”
Section: Discussionmentioning
confidence: 71%
“…She complained of severe depressive symptoms, had a handful of hair fall every day, presented with insomnia, and was inclined to commit suicide [140]. The safety of the Motiva Ergonomix TM Round SilkSurface was confirmed in a cohort of Korean women, as previously described [85,86,141]. It was previously reported that the Motiva Ergonomix TM Round SilkSurface might be a device of choice for Korean women who faced a crisis from the first Korean case of a medical device fraud [86].…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, the Motiva Ergonomix TM Round SilkSurface might be the device of choice for Korean women who have been faced with the BIA-ALCL crisis and the first Korean case of medical device fraud [ 24 , 70 ]. The cost of the Motiva Ergonomix TM Round SilkSurface is the highest, although it triggered a boom in microtextured devices [ 71 ]. As described above, 15,570 and 9732 devices were sold by Mentor Worldwide LLC.…”
Section: Resultsmentioning
confidence: 99%
“…and Establishment Labs Holdings Inc., respectively, between January and June of 2021 [ 23 ]. Considering that their costs are USD 5070.01 and 8450.02 in corresponding order, it can be inferred that the total revenue of their sales reached USD 78,940,055.7 and 82,235,594.64 [ 71 ]. This indicates that the Motiva Ergonomix TM Round SilkSurface is the most popular brand of SGBI in Korea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study mainly compared various silicone gel implant products, but there was no comparison or analysis of smooth and microtextured silicone gel implants and no statistical significance was found between groups. 23 Tanner reported that the incidence of capsular contracture was low as a result of analyzing the clinical results of 214 patients who used microtextured silicone gel implants in breast cosmetic surgery. However, that study also did not compare smooth and microtextured silicone gel implants.…”
Section: Discussionmentioning
confidence: 99%